Vacuum infiltration of copper aluminate by liquid aluminium - Guedes, M.; Rocha, Luís Augusto Sousa Marques da [UNESP]; Ferreira, J. M. F.; Ferro, A. C. (Elsevier, 2011)
This paper studies attained microstructures and reactive mechanisms involved in vacuum infiltration of copper aluminate preforms with liquid aluminium. At high temperatures, under vacuum, the inherent alumina film enveloping the metal is overcome, and aluminium is expected to reduce copper aluminate, rendering alumina and copper. Under this approach, copper aluminate toils as a controlled infiltration path for aluminium, resulting in reactive wetting and infiltration of the preforms. Ceramic preforms containing a mixture of Al2O3 and CuAl2O4 were infiltrated with aluminium under distinct vacuum levels and temperatures, and the resulting reaction and infiltration behaviour is discussed. Copper aluminates stability ranges depend on vacuum level and oxygen partial pressure, which determine both CuAl2O4 and CuAlO2 ability for liquid aluminium infiltration. At 1100 °C and 0.76 atm vacuum level CuAl2O4 is stable, indicating pO2 above 0.11 atm. Reactive infiltration is achieved via reaction between aluminium and CuAl2O4; however, fast formation of an alumina film blocking liquid aluminium wicking results in incipient infiltration. At 1000 °C and 3.8 × 10−7 atm vacuum level, CuAlO2 decomposes to Cu and Al2O3 indicating a pO2 below 6.0 × 10−7 atm; infiltration of the ceramic is hindered by the non-wetting behaviour of the resulting metal alloy. At 1000 °C and 1.9 × 10−6 atm vacuum level CuAlO2 is stable, indicating pO2 above 6.0 × 10−7 atm. Extensive infiltration is achieved via redox reaction between aluminium and CuAlO2, rendering a microstructure characterised by uniform distribution of alumina particles amid an aluminium matrix. This work evidences that liquid aluminium infiltration upon copper aluminate-rich preforms is a feasible route to produce Al–matrix alumina-reinforced composites. The associated reduction reaction renders alumina, as fine particulate composite reinforcements, and copper, which dissolves in liquid aluminium contributing as a matrix strengthener.
Keywords: B. Composites; B. Microstructure-final; D. Spinels; Reactive aluminium infiltration